SELJUK ERA STYLE (IN THE FIFTH AND SEVENTH CENTURES AH) (ELEVENTH AND THIRTEENTH CENTURES AD) (A) IRAN (b) TURKEY (c) ATABEK - Dr. Raad Mutar Majeed, Sahar Raoof Saeed Altaher, Atheer Sabah Hussein (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The Seljuk Turks belonged to the nomadic Turkmen tribes that migrated from the wilds of the Kyrgyz Republic in Central Asia. He began to embrace the Turks of Central Asia Islamic religion since the eighth century, but the spread of new , including religion collectively not only in the atheist century, and was therefore a great impact in the history of Islam, where he held the Turkish element since that period , a major center in the Muslim world , As a result of the division that prevailed in the countries of the Islamic world, the Seljuk Turks came out, and they were able to conquer the countries of Iran, the Levant, the Jazira and Iraq, and they made them all under the rule of one person, and an independent sect of the Seljuks established their kingdoms in Persia, Azerbaijan, the Jazira and Diyarbakir and knew these by intertwining. From this quick overview, it becomes clear that Persian families, and others of Turkish origin, have come to rule Iran.